2017
DOI: 10.20473/ijph.v11i1.2016.40-50
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Pelatihan, Motivasi Dan Ketersediaan Fasilitas Dengan Partisipasi Jumantik Di Kota Blitar

Abstract: In Dengue Hemorrhagic Fever (DHF) is a health problem and the number of cases is increasing every year, including in East Java. Blitar City is one of the cities in East Java which is endemic dengue. The Incident Rate (IR) in 2015 which is 70,28 per 100.000 population over the target area that is 21 per 100.000 population. One effort that can be done to reduce the number of dengue cases is increasing activeness jumantik in the prevention of dengue. Jumantik task in the prevention of dengue fever include CHD (Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Hal ini sejalan dengan penelitian yang dilakukan oleh Yunita (2016) yang menyatakan bahwa terdapat hubungan antara ketersediaan fasilitas dengan partisipasi jumantik di Kota Blitar. 19 Hasil berbeda ditunjukkan pada penelitian yang dilakukan oleh Najman (2020) bahwa tidak ada hubungan yang signifikan antara sarana dan dana dengan kesiapsiagaan petugas kesehatan dalam menghadapi kejadian luar biasa DBD Puskesmas Biru Kabupaten Bone. 20 Sarana adalah sumber daya penting selain tenaga dan dana untuk menjalankan kegiatan yang disusun dengan baik.…”
Section: Bahasanunclassified
“…Hal ini sejalan dengan penelitian yang dilakukan oleh Yunita (2016) yang menyatakan bahwa terdapat hubungan antara ketersediaan fasilitas dengan partisipasi jumantik di Kota Blitar. 19 Hasil berbeda ditunjukkan pada penelitian yang dilakukan oleh Najman (2020) bahwa tidak ada hubungan yang signifikan antara sarana dan dana dengan kesiapsiagaan petugas kesehatan dalam menghadapi kejadian luar biasa DBD Puskesmas Biru Kabupaten Bone. 20 Sarana adalah sumber daya penting selain tenaga dan dana untuk menjalankan kegiatan yang disusun dengan baik.…”
Section: Bahasanunclassified
“…In other words, performance is an important factor that an organization needs to pay attention to because it may affect the goal achievement of the organization as well as the fluctuated progress of the organization to face the global competition. Performance refers to the carrying out actions and perfecting them as one's responsibility to achieve desirable results [10], [11]. It means that a good performance can be observed through the results that one achieves, in accordance with the work standard of the organization or the workplace he/ she works at.…”
Section: A the Factor That Was Proven To Have A Relationship Withmentioning
confidence: 99%
“…Another study [10], found that training could improve a worker's skills, leading to improved work result according to the standard being applied. It also showed that there was a relationship between training and the participation of larvae surveyor with PR value of 1.933 [10].…”
Section: ) the Relationship Between Training And Larvae Surveyor Permentioning
confidence: 99%